Analysis of factors of Low Student Learning Interest in Grade IV Mathematics Subjects at Elementary School - Arni, Yusni; Andriani, Fitri; Maharani, Inka; Widhiyani, Ni Nyoman Revi (Pusdikra-Publishing.com, 2024)
A study was conducted by researchers at SD Negeri 35 Palembang. The purpose of this study was to examine the various factors that cause students' lack of interest in learning in grade IV in mathematics. The researcher utilized a qualitative research method using a case study approach. Data collection was done through triangulation and inductive analysis, and emphasis on meaning rather than generalization in qualitative research results. Case study refers to a series of research activities carried out in a structured, detailed, and thorough manner regarding a program, event, or activity. The purpose of this case study is to understand in depth about it, both from the perspective of individuals, groups, institutions, and organizations. Generally, the case chosen is an ongoing event in real life, not something that has happened in the past. The process of collecting information is carried out through direct observation and interaction through interviews. Based on observations, interviews, and notes taken by the researcher, it was concluded that there were about five students in one class who received low scores and lacked interest in learning mathematics. Based on information found by researchers during observations and interviews, it can be concluded that there are several reasons why grade IV students' interest in learning mathematics at SD Negeri 35 Palembang is low. First, students do not have enough rest time. Second, students lack motivation to learn. Third, students do not show high interest in math. Fourth, students have to deal with two activities at once, namely school and boarding school. Finally, there is the influence of the post-Covid-19 situation or online learning.